Watership Down - Adams, Richard, 1920-2016 (New York : Scribner, 2018)
Richard Adams's Watership Down is a timeless classic and one of the most beloved novels of all time. Set in the Hampshire Downs in Southern England, an idyllic rural landscape, this stirring tale of "suspense, hot pursuit, and derring-do" (Chicago Tribune) follows a band of rabbits in flight from the incursion of man and the destruction of their home. Led by a stouthearted pair of brothers, they travel forth from their native Sandleford warren through harrowing trials to a mysterious promised land and a more perfect society. "A marvelous story of rebellion, exile, and survival" (Sunday Telegraph) this is an unforgettable literary classic for all ages. -- Amazon.
Originally published: Rex Collings, 1972.
"Now a major Netflix series"--Cover.
Keywords: Rabbits -- Fiction; Adventure stories; Fantasy fiction